VILLAGE GOVERNANCE IN THE IMPLEMENTATION OF THE GREENHOUSE PROGRAM: AN ANALYSIS OF INSTITUTIONAL ROLES AND POLICY EFFECTIVENESS IN KLASEMEN VILLAGE, PROBOLINGGO REGENCY - Sari, Vivi Yunika; Puspitarini, Renny Candradewi; Maksin, Mastina; Sucahyo, Imam (Jurnal PUBLIQUE, 2026)
The transformation of the agricultural sector in rural areas is increasingly confronted with structural pressures arising from climate change, resource constraints, and the declining participation of younger generations in agricultural activities. These conditions necessitate the development of adaptive and sustainable agricultural innovations, one of which is the implementation of greenhouse systems. This study aims to analyze the role of village government in the implementation of the Greenhouse Program in Klasemen Village, Probolinggo Regency, employing Sondang P. Siagian’s theory of governmental roles, which encompasses the functions of facilitator, regulator, motivator, and dynamizer. A descriptive qualitative approach was adopted, with data collected through observation, interviews, and documentation, and analyzed using an interactive analysis technique. The findings indicate that the village government performs an integrated and strategic role in supporting the success of the program. As a facilitator, the village government provides infrastructure, administrative support, and access to external networks. As a regulator, it establishes rules and management mechanisms that ensure orderly program implementation. As a motivator, it fosters changes in community mindset and enhances farmers’ participation in adopting agricultural innovations. Meanwhile, as a dynamizer, it sustains program continuity through active involvement, strengthened collaboration, and the maintenance of group dynamics among farmers. These findings demonstrate that the success of the Greenhouse Program is not solely determined by technical aspects but is also significantly influenced by the institutional capacity of the village government in integrating administrative and social functions simultaneously. This study contributes to the enrichment of public administration literature, particularly in the context of village governance in implementing community-based agricultural innovations. Furthermore, the findings offer practical insights for the formulation of village-level policies aimed at strengthening food security and promoting sustainable development at the local level.